Re-education of the Tumor Microenvironment With Targeted Therapies and Immunotherapies - Ngiow, Shin Foong; Young, Arabella (Frontiers in Immunology, 2020)
The clinical success of cancer immunotherapies targeting PD-1 and CTLA-4 has ignited a substantial research effort to improve our understanding of tumor immunity. Recent studies have revealed that the immune contexture of a tumor influences therapeutic response and survival benefit for cancer patients. Identifying treatment modalities that limit immunosuppression, relieve T cell exhaustion, and potentiate effector functions in the tumor microenvironment is of much interest. In particular, combinatorial therapeutic approaches that re-educate the tumor microenvironment (TME) by limiting the accumulation of immunosuppressive immune cells, such as Foxp3 regulatory T cells (Tregs) and tumor-associated macrophages (TAMs), while promoting CD8+ and CD4+ effector T cell activity is critical. Here, we review key approaches to target these immunosuppressive immune cell subsets and signaling molecules and define the impact of these changes to the tumor milieu. We will highlight the preclinical and clinical evidence for their ability to improve anti-tumor immune responses as well as strategies and challenges for their implementation. Together, this review will provide understanding of therapeutic approaches to efficiently shape the tumor microenvironment and reinvigorate the immune response against cancer.